MEMBERDAYAKAN KELOMPOK MASYARAKAT YANG MISKIN, MELALUI SIKLUS SEKOLAH NONFORMAL, DALAM UPAYA MENINGKATKAN KESEJAHTERAAN SOSIAL DI KABUPATEN ENREKANG - Jusni Hastriani; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2021)
The exploration objective was to decide the strengthening cycle through non-formal instruction in completing preparing exercises for the poor to improve social government assistance in Enrekang Rule. Subjective examination, phenomenological approach, research tests, Fadel Center for Community Learning Activities(CCLA),Merpati Center for Community Learning Activities,Nurul Hidayah Center for Community Learning Activities, Salu Bulo Center for Community Learning Activities and Spnf SKB Enrekang, respondents, organization directors, poor people or learning residents, and local area pioneers. Information assortment, perception strategies, and meetings. The consequences of the exploration are (1) the strengthening cycle completed by non-formal instructive organizations has not coordinated with the assumptions for the learning residents associated with the interaction, and has not focused on the parts of the necessities needed by the learning residents, (2) the outcomes created subsequent to taking part in the strengthening cycle in foundations Non-formal training has not assisted the poor with improving their lives, and (3) the helpful relationship that has been set up by Fadel Center for Community Learning Activities, Merpati Center for Community Learning Activities, Nurul Hidayah Center for Community Learning Activities, Salu Bulo Center for Community Learning Activities and Spnf SKB Enrekang is restricted to neighborhood governments.